Factors affecting rental use in the lower Silesia province during the pandemic period - Olena Ivashko; Kamila Urbańska; Arkadiusz Górski; Agnieszka Parkitna; Olgierd Jeż (Journal of Modern Science)
Objectives The article focuses on the analysis and evaluation of changes in tenant behavior and expecta-tions, in the rental market during constraints on the operation of, among others, institutions, businesses, and schools, during the pandemic. The behavior of young people, who, by defini-tion, base their housing needs more heavily on rent, was analyzed. The purpose of the article is to analyze the factors that affect the use of rent by young people in the Lower Silesian province during the pandemic. This research paper attempted to answer in what direction these changes have gone. In the process of designing the study, research hypotheses were formulated. Based on statistical analysis, it was assumed that the key factor that affects long-term rent use is lack of creditworthiness